KELAYAKAN TEORITIS LKS PRAKTIKUM BERBASIS PENEMUAN TERBIMBING PADA MATERI PENCEMARAN AIR UNTUK SMA KELAS X - AZIZAH, LAILATUL (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
The lack of sensitivity of 10th grade senior high school studentsin the problem of water pollutionand lack of understanding of the student in that matter makelearning less meaningful. It takes a learning device in the form of student worksheet guided discovery-based lab to foster student sensitivity to the problems of water pollution.This study aims to produce a student worksheets guided discovery-based lab on water pollution materials for 10th grade senior high school students and describe the theoretical feasibility of worksheets based on expert judgments. The results showed that the developed worksheets that are feasible in theory with the results of the study of 87.2%. Keywords:the matter of water pollution, a student worksheets guided discovery-based lab, theoretical feasibility